MODIFICATION OF DOCUMENTATION IN THE CONTEXT OF DIGITALIZATION OF ACCOUNTING - Shkromyda, V.V.; Shkromyda, N.Ya.; Gnatyuk, T.M. (The actual problems of regional economy development, 2023)
The article examines the changes and additions that arise in the process of documenting business processes at the enterprise in the context of digitalization of accounting and reporting. Thanks to the rapid development of technologies and the introduction of digital tools, accounting is transformed from a traditional paper process into an automated electronic system that brings a number of advantages to the work of the enterprise. The key advantages of digitization of accounting include the accuracy of accounting data, convenient and quick access to them, as well as a high level of protection and security. A positive aspect at the state level is that a number of legislative acts have been adopted in the direction of the use of digital technologies in accounting and reporting. This creates a favorable basis for the deployment and acceleration of the process of digital transformation in the field of accounting and financial reporting, as well as economic relations. In the conditions of digitization of accounting and reporting, there is an increase in the details of electronic accounting documents that did not exist in paper format before. This process is accompanied by the transfer of document circulation to the virtual space. With the help of extended metadata, the electronic format provides an opportunity to change the structure, content and order of documents in real time and quickly. In addition, the digitalization of accounting improves the conditions for the organization of document circulation in the enterprise. It allows you to apply an object-oriented approach to the construction of document circulation, which means that electronic documents can move both vertically (along the hierarchical chain of confirmation) and horizontally (between different departments and structural units). This makes it possible to quickly adapt the routes of passing documents depending on the objects being documented and the production needs that change at the enterprise. The obtained scientific results will contribute to the development of the theoretical and methodological basis of the process of evaluating the effectiveness of the implementation of digital documentation at the enterprise and finding ways to improve the efficiency and reliability of accounting and analytical information.